A lytic monoclonal antibody to Trypanosoma cruzi bloodstream trypomastigotes which recognizes an epitope expressed in tissues affected in Chagas' disease. - Zwirner, N W (1994)
It has been suggested that molecular mimicry between the antigens of Trypanosoma cruzi and the host could have a role in the onset of the chronic stage of Chagas' disease. In this article, we report on a monoclonal antibody (MAb), CAK20.12 (immunoglobulin G2b), which reacts with a polypeptidic epitope of a 150-kDa antigen expressed on the surface of several strains of T. cruzi. This MAb also causes lysis of bloodstream trypomastigotes. Serum samples from 30 of 30 patients with chronic and 11 of 13 patients with acute Chagas' disease present specific antibodies to this antigen. MAb CAK20.12 reacts, by indirect immunofluorescence, with human and syngeneic murine striated muscle tissue, with the smooth muscle layer of cardiac arteries, with the lamina muscularis mucosae and the external striated muscle layer of the esophagus, and with the smooth muscle cells of the colon from normal syngeneic mice. Reactivity with the small intestine was very weak, and no reactivity with ventricle or atrium tissue was detected. Adsorption with an antigenic fraction from normal murine striated muscle or from T. cruzi epimastigotes confirmed that MAb CAK20.12 recognizes a common epitope present in parasites and host tissues. MAb CAK20.12, lytic for the infective form of T. cruzi, recognizes an epitope expressed in striated and smooth muscle cells of the host tissues affected in the chronic stage of Chagas' disease.